Lo único permanente es el cambio - Piscoya, Alejandro (2020)
After just over two years of assuming the challenge to manage our journal, we have continue changing, bit by bit, in order to fulfil our goals.This is going to be the first number with Digital Object Identifier (DOI) system, we planned to do this for a long time but will never get the time to implement it, but, finally, SciELO came to the rescue and, even though DOI were mandatory since 2015, now it has decided to ask their journals to fulfil this criteria (1). DOI is essential to increase visibility and interoperability ofall journals listed in SciELO and now is mandatory. We are starting with all our articles for this year and later will continue with prior years.